Another face of violence against women: Infertility - Ozturk, Rusen (Pak J Med Sci, 2017)
BACKGROUND & OBJECTIVE: Violence against women is a widespread problem and has serious implications on women’s health. Infertility, in many ways, is a very stressful condition that affect social and marital life of a couple; moreover, compared to fertile women, infertile women are twice as vulnerable against violence. Our objective was to determine the prevalence of violence and define the effect of infertility on violence on women receiving infertility treatment. METHODS: Descriptive and cross-sectional study was carried out 301 infertile women between November 2015 and August 2016 in a state hospital, Izmir. Data were collected as “Sociodemographic Characteristics Form” and “Infertile Women’s Exposure to Violence Determination Scale”. RESULTS: The mean age of women was 31.77±5.46 years; the average duration of marriage was 6.93±4.53 years. About 32.5% of women stated that they have suffered from violence throughout their lives and 4.7% of women were still suffering from violence, while 5.0% of women were subjected to violence after infertility was diagnosed. CONCLUSION: It is an encouraging finding that infertile women have a low exposure to violence. However, despite a low violence rate, there is an increase in violence toward women who have been diagnosed with infertility.